The dynamics of distributive politics - Marco Battaglini; Thomas R. Palfrey (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2007)
We study dynamic committee bargaining over an infinite horizon with discounting. In each period a committee proposal is generated by a random recognition rule, the committee chooses between the proposal and a status quo by majority rule, and the voting outcome in period t becomes the status quo in period t+1. We study symmetric Markov equilibria of the resulting game and conduct an experiment to test hypotheses generated by the theory for pure distributional (divide-the-dollar) environments. In particular, we investigate the effects of concavity in the utility functions, the existence of a Condorcet winning alternative, and the discount factor (committee impatience). We report several new findings. Voting behavior is selfish and myopic. Status quo outcomes have great inertia. There are strong treatment effects, that are in the direction predicted by the Markov equilibrium. We find significant evidence of concave utility functions.
Keywords: D71; D72; C78; C92; 330; Dynamic bargaining; voting; experiments; divide-the-dollar; committees; Einkommensumverteilung; Dynamisches Spiel; Verhandlungstheorie; Theorie